Influence of Job Characteristics as a Motivation Strategy on the Academic Achievement of Teachers in Secondary Schools in Kisii Central Sub-County, Kenya - Norah Moraa Osano; Christopher Makworo Ayienda (IJRDO- Journal of Educational Research, 2020)
This study sought to determine teacher motivation strategies on student academic achievement in secondary schools in Kisii Central Sub-County, Kenya. The study majored on the effects of job characteristics as a motivation strategy on the academic achievement of teachers in secondary schools in Kisii Central Sub-County of Kisii County. The study was guided by Herzberg’s (1966) Two Factor Theory which divides motivation and job satisfaction into two groups of factors known as the motivation factors and hygiene factors. This theory is suitable for this study because it addresses both intrinsic and extrinsic ways of improving teacher motivation. The research methodology for this study was quantitative method combined with descriptive survey design. The study targeted all the forty-five principals of the secondary schools in Kisii Central Sub-County, BOM heads and teachers in secondary schools in Kisii Central Sub-County. The entire population was sampled using simple random sampling technique; where 16 schools out of the 48 secondary schools in the sub-county were sampled. Purposive sampling was used to select data from BOM heads of the respective schools. The research instruments used were questionnaires and interview schedules. The questionnaires were used on teachers and interviews on principals of various secondary schools. Descriptive statistics such as percentages, means and frequencies were used. The study established that job characteristics as a motivation strategy on the academic achievement of teachers, the study showed that principals need to create opportunities for growth, ensure there is job security and set goals and objectives. The study recommended that principals needs to communicate the school policy to the teachers to ensure clarification and presence of a common understanding by teachers. Inferential statistics showed that protecting teachers from job insecurity inconveniences and guidance and counseling has a positive effect in improving teacher motivation.